Impatiens bullatisepala (Balsaminaceae), a new species from Guizhou, China - Peng, Shuai; Cong, Yi-Yan; Tian, Jing; Zhang, Cai-Fei; Hu, Guang-Wan; Wang, Qing-Feng (Phytotaxa, 2021)
Impatiens bullatisepala (Balsaminaceae), a new species supported by morphological and phylogenetic evidence from Fanjing Mountain, Guizhou province in China, is described here. It is morphologically similar to I. davidii but can be distinguished by its dorsally ridged lateral sepals with sunk reticulate veins and bullate projections on abaxial surface, 2–2.5 cm deep saccate lower sepal with ca. 0.8 cm long narrowly triangular tip at the mouth, and broadly ovate dorsal petal. Phylogenetic analyses of a combined dataset of nuclear ITS and plastid atpB-rbcL intergenic spacer DNA sequences furtherly confirmed its novelty.